How to evaluate shelters for archaeological sites: some recommendations based on the use of exposure trials - Cabello Briones, Cristina (Ge-conservacion, 2017)
Shelters are commonly considered effective preventive conservation methods for excavated archaeological sites. However, archaeological remains covered with shelters are still deteriorating in many cases, and the shelters can even exacerbate the damage. Therefore, regular evaluations of the shelter behaviour are extremely important. This paper presents a summary of the main approaches to shelter performance assessment carried out to date. In addition, the application of geomorphological methods to heritage conservation has been reviewed. The objective is to determine their suitability for the evaluation of shelters. This paper also presents the main results from the study on the shelters at the Bishop´s Palace (Witney, England) and Hagar Qim (Malta) on limestone conservation using exposure trials. To conclude, recommendations based on the case-study sites have been made to improve the effectiveness of future approaches.